2010
DOI: 10.1080/08946566.2010.490188
|View full text |Cite
|
Sign up to set email alerts
|

Education and Training of Mandated Reporters: Innovative Models, Overcoming Challenges, and Lessons Learned

Abstract: Several Archstone Foundation funded projects developed and implemented training curricula on elder abuse for mandated reporters such as dentists, adult protective services workers, paramedics, and coroner investigators. Common education and training issues emerged, including the need to provide basic content on normal aging and the need for creating standardized trainings. Strategies include integrating elder abuse and neglect content into existing courses, building relationships with stakeholders, and customi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 3 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…One of the systematic reviews included in this review (Cooper et al, 2009) concluded that no study has investigated how rates of detection and reporting could be increased, but did suggest a relationship between whether professionals received training and a higher likelihood of reporting suspected abuse. The analysis of the existing evidence (Bond, 2004;Cooper, Huzzey, & Livingston, 2012;Dow et al, 2013;Gironda et al, 2010;Shefet et al, 2007;Strümpel & Hackl, 2011;Sugita & Garrett, 2012) indicates some features that training programmes on detection and reporting of elder abuse should include: clear procedures regarding how to act and how to report abuse are in place before training courses are conducted; to include information about the ageing process to allow contextualisation of abuse cases; adaptation of content to existing regulations; training tailored to the characteristics and needs of the participants; the consideration of the importance of cultural aspects; flexible planning that suits the schedules of the participants and offers a number of appropriate training times to achieve the desired level of learning; the inclusion of different professional profiles, as well as volunteers, to enhance the training experience and provide a foundation for networking between individuals from different professions; the discussion of cases encountered in daily work to facilitate learning; to favour professionals asking seniors about abuse and addressing professionals' concerns about the impact of reporting abuse on their therapeutic relationship with victims and the legal consequences for informants; and the use of standardised patients as the one methodology that can facilitate acquisition of relevant skills.…”
Section: The Ability Of Knowledge and Attitudes Of Professionals To Amentioning
confidence: 99%
“…One of the systematic reviews included in this review (Cooper et al, 2009) concluded that no study has investigated how rates of detection and reporting could be increased, but did suggest a relationship between whether professionals received training and a higher likelihood of reporting suspected abuse. The analysis of the existing evidence (Bond, 2004;Cooper, Huzzey, & Livingston, 2012;Dow et al, 2013;Gironda et al, 2010;Shefet et al, 2007;Strümpel & Hackl, 2011;Sugita & Garrett, 2012) indicates some features that training programmes on detection and reporting of elder abuse should include: clear procedures regarding how to act and how to report abuse are in place before training courses are conducted; to include information about the ageing process to allow contextualisation of abuse cases; adaptation of content to existing regulations; training tailored to the characteristics and needs of the participants; the consideration of the importance of cultural aspects; flexible planning that suits the schedules of the participants and offers a number of appropriate training times to achieve the desired level of learning; the inclusion of different professional profiles, as well as volunteers, to enhance the training experience and provide a foundation for networking between individuals from different professions; the discussion of cases encountered in daily work to facilitate learning; to favour professionals asking seniors about abuse and addressing professionals' concerns about the impact of reporting abuse on their therapeutic relationship with victims and the legal consequences for informants; and the use of standardised patients as the one methodology that can facilitate acquisition of relevant skills.…”
Section: The Ability Of Knowledge and Attitudes Of Professionals To Amentioning
confidence: 99%
“…Many studies have identified raised staff awareness of maltreatment via educational initiatives. 88 , 89 However, these studies tend to be single-point evaluations, many undertaken at the end of the training program, where sensitivity to maltreatment is heightened. Some studies identified the limitations of current educational programs 89 with Smith et al 90 emphasizing that a focus on more interactive and personally relevant programs has the ability to imbue a deeper understanding of the issue.…”
Section: Education and Trainingmentioning
confidence: 99%
“…While complex, these approaches can be applied effectively to readily available administrative or census data to produce estimates of average health literacy and identify communities that would benefit most from appropriate targeted interventions in specific clinical settings, and to address poor quality care and outcomes related to low health literacy [2]. Standardized and targeted training strategies can be effective in building stronger relationships with stakeholders, particularly when designed to customize practice-based content and curriculum delivery to patient's optimal cognitive learning mode and preferences [3]. …”
Section: Background and Descriptionmentioning
confidence: 99%